The new provisions for the seismic design of timber buildings in Europe. (1st August 2018) - Follesa, M.; Fragiacomo, M.; Casagrande, D.; Tomasi, R.; Piazza, M.; Vassallo, D.; Canetti, D.; Rossi, S.
Highlights: A review of the different previous versions of Chapter 8 of Eurocode 8 is presented. New definition of structural types is presented with graphical description. Capacity design rules, ductility provisions and over-strength factors are presented for the different structural types. Other changes including modified definitions, material properties and safety verifications equations are presented. Some provisions regarding the application of non-linear static analysis of timber structures is introduced. Abstract: This paper presents the results of the ongoing work on the revision of the provisions for the seismic design of timber buildings in Europe included within Chapter 8 of Eurocode 8. The most recent research results and technical developments regarding both wood-based materials and structural systems have been implemented into the proposed new version together with the application of the capacity design to each structural system. The main objectives are to update the few and incomplete provisions included in the current version to the current state-of-the-art and to correct some misleading rules. This manuscript represents the authors' point of view on the basis of a scientific research background and the design common practice regarding different key aspects in the seismic design of timber structures.